Sham Litigation, Delayed Tax Payment and Evasion: The Role of Informal Credit Market - Sugata Marjit; Suryaprakash Mishra; Sandip Mitra (Center for Economic Studies and ifo Institute (CESifo), 2019)
We model the interaction between the informal credit market and the act of tax collection by the government; in presence and functioning of the informal credit market, the agents (the tax paying firms) engage in false or sham litigation and deferred tax payments. During the litigation period they earn higher return, higher than the punishment rates charged by the government. Proportion of false claims increases with size. In this context we get a result that contradicts conventional wisdom in tax evasion literature whereby higher tax rate actually leads to greater compliance and tax rate acts as a policy instrument even when in the standard case it does not affect evasion. We propose part-payment of the disputed amount by the tax paying firm to the government as a possible solution to the problems of excessive litigation against the government, delayed tax payments and evasion; it also has a positive impact on the tax collection of the government. Finally, we also attempt to explain as to why and how the government policies may be intentionally designed to foster the informal sector.
Keywords: H25; H26; H32; K34; K41; K42; 330; delayed tax payment; evasion; sham litigation; informal credit market